1997
DOI: 10.1063/1.474453
|View full text |Cite
|
Sign up to set email alerts
|

Connection between quasielastic Raman scattering and free volume in polymeric glasses and supercooled liquids

Abstract: Quasielastic light scattering (QLS) in the frequency interval 100–1000 GHz is measured in some polymers: polycarbonate, polybutadiene, polystyrene, and poly(methyl methacrylate). To describe the spectra, a model of the fast picosecond relaxation processes responsible for the QLS, which is based on the damping of the boson peak vibrations by the dynamic hole volume fluctuations, is used. Within the frame of the model, the intensity of the fast relaxation process is proportional to the fractional dynamic hole vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
74
0
6

Year Published

2004
2004
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 91 publications
(87 citation statements)
references
References 41 publications
7
74
0
6
Order By: Relevance
“…41,85 In low-frequency Raman spectroscopy, it is known that the temperature dependence of the QES intensity, I QES , in the supercooled liquid range is steeper than below T g . [27][28][29][30][31][32][33][34][57][58][59][60] The change of slope of the I QES (T) curve at T g is at first sight a remarkable finding, since QES is related to processes taking place at picosecond time scale while the glass transition is due to the structural α-relaxation time, τ α , reaching 10 2 -10 3 s. In fact, the relationship between I QES and α-relaxation is another example of these correlations between fast and slow dynamics of glassforming liquids.…”
Section: Fragility Of Glass-forming Liquids M = Dln[η(t)]/d(t G /T) mentioning
confidence: 98%
See 4 more Smart Citations
“…41,85 In low-frequency Raman spectroscopy, it is known that the temperature dependence of the QES intensity, I QES , in the supercooled liquid range is steeper than below T g . [27][28][29][30][31][32][33][34][57][58][59][60] The change of slope of the I QES (T) curve at T g is at first sight a remarkable finding, since QES is related to processes taking place at picosecond time scale while the glass transition is due to the structural α-relaxation time, τ α , reaching 10 2 -10 3 s. In fact, the relationship between I QES and α-relaxation is another example of these correlations between fast and slow dynamics of glassforming liquids.…”
Section: Fragility Of Glass-forming Liquids M = Dln[η(t)]/d(t G /T) mentioning
confidence: 98%
“…[57][58][59][60] It has been already shown that both the models give good fit to 31 but these models need assumptions concerning the functions to be used in fits. Thus, we follow here instead a less model dependent procedure, and we considered I QES as the integral up to the boson peak, say 4 < ω < 20 cm −1 , of the experimental spectrum normalized by intensity of high frequency bands.…”
Section: Fragility Of Glass-forming Liquids M = Dln[η(t)]/d(t G /T) mentioning
confidence: 99%
See 3 more Smart Citations